Methanesulfonic acid and sulfuric acid Aerosol Formed through oxidation of reduced sulfur compounds in a humid environment. (15th September 2021) - Van Rooy, Paul; Drover, Ryan; Cress, Tanner; Michael, Cara; Purvis-Roberts, Kathleen L.; Silva, Philip J.; Nee, Matthew J.; Cocker, David
Abstract: Particulate sulfuric acid and methanesulfonic acid (MSA) are known to form through oxidation of reduced sulfur compounds, however, the mechanisms by which these compounds form are not well understood. Additionally, the aerosol yields and ratio of MSA to sulfuric acid particulate formation are not well documented, making it difficult to estimate the health and climate impacts of reduced sulfur compounds. To investigate these unknowns, dimethylsulfide (DMS) and dimethyldisulfide (DMDS) were oxidized, using a variety of oxidants, in a 37.5 cubic meter Teflon environmental chamber with relative humidity ranging from 2% to 55%. The mass fraction of particulate MSA was estimated based on unique aerosol fragments, at m/z 79 and 96, measured by a High Resolution Time-of-Flight Mass Spectrometer. MSA to sulfuric acid particulate ratios varied depending on initial conditions. This study revealed that substantial water vapor is necessary to form MSA. The mass fraction of MSA increases in the presence of NO x . Nitrate radical oxidation of DMS and DMDS resulted in nearly 100% of the aerosol estimated to be MSA, suggesting nighttime chemistry may play an important role in ambient MSA formation. This study builds upon results from similar experiments, presented in Van Rooy et al. (2021), which were conducted under extreme dry conditions. Highlights: Dimethysulfide (DMS) and dimethyldisulfide (DMDS) were oxidized in an environmental chamber with RH ranging from 2% to 55%. Mass fraction of methanesulfonic acid (MSA) particulate was calculated using unique particle fragments at m/z 79 and m/z 96. DMS required both NOx and humidity to form MSA. DMDS required humidity to form MSA; NOx enhanced the mass fraction of MSA.